Investor–State Dispute Settlement Reform and Theory of Institutional Design. (13th June 2018) - Dimitropoulos, Georgios
ABSTRACT: The article discusses the issue of reform in Investor–State Dispute Settlement (ISDS) through the lens of the theory of heuristics and biases identified by cognitive psychology and behavioural economics. Reform proposals in ISDS have been heavily path-dependent on past theories and existing institutions in the field of international adjudication. A behavioural theory of international institutions can help design ISDS mechanisms that are better suited to the actual decision-making processes in international adjudication. The article presents various debiasing instruments for the ISDS context, such as 'nudges', which could form part of the institutional design of the new dispute resolution fora together with rational design instruments. Transparency mechanisms, levels of review, training and evaluation, consider-the-opposite strategies and new legal default rules should become embedded in the reformed ISDS, alongside a pluralistic rather than specialized court structure.